Investigating the interaction of preosteoblast cells with poly-L lysine surface-modified chitosan/hydroxyapatite scaffolds and their potential applications in bone tissue engineering - Mutlu, Tugce Kan; Ozcinar, Betul Mutlu; Koksal, Ismet; Cakir, Rabia (ELSEVIER SCI LTD, 2025)
Bone is a multifunctional organ that undergoes constant structural and biological changes. In cases of damage due to trauma, cancer, infection or hormonal imbalances, medical intervention is required for bone regeneration. This study aims to develop a tissue scaffold that promotes bone tissue regeneration by enhancing cell adhesion, proliferation, and mineralization. For this purpose, tissue scaffolds with varying contents were produced using chitosan (Ch), hydroxyapatite (HA), and poly-L-lysine (PLL) as scaffold materials by freeze-drying method and characterized. In studies conducted to evaluate the biological activities of the scaffolds on MC3T3-E1 preosteoblast, the PLL-Ch/HA 1:2 scaffold exhibited approximately 20 % higher cell viability than the control on days 3 and 7 of extract analysis. In cells cultured on the scaffold, PLL-coated Ch/HA scaffolds showed a greater proliferative effect than uncoated Ch/HA scaffolds on day 7 of culture, resulting in a significant increase in cell viability. Furthermore, the observed increase in calcification and mineralization when cells were cultured on PLL-modified scaffolds could be attributed to PLL promoting cell adhesion and proliferation, resulting in increased calcium deposition. The surface modification of Ch/HA composite scaffolds with PLL has revealed optimal performance in bone tissue engineering due to their favorable performance.
Keywords: Bone tissue engineering; Chitosan; Hydroxyapatite; Poly-L-lysine; Scaffold; ADHESION; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering